The G1662S NaV1.8 mutation in small fibre neuropathy: impaired inactivation underlying DRG neuron hyperexcitability. Issue 5 (4th September 2013) - Han, Chongyang; Vasylyev, Dmytro; Macala, Lawrence J; Gerrits, Monique M; Hoeijmakers, Janneke G J; Bekelaar, Kim J; Dib-Hajj, Sulayman D; Faber, Catharina G; Merkies, Ingemar S J; Waxman, Stephen G
Abstract : Objective: Painful small fibre neuropathy (SFN) represents a significant public health problem, with no cause apparent in one-half of cases (termed idiopathic, I-SFN). Gain-of-function mutations of sodium channel NaV 1.7 have recently been identified in nearly 30% of patients with biopsy-confirmed I-SFN. More recently, gain-of-function mutations of NaV 1.8 have been found in patients with I-SFN. These NaV 1.8 mutations accelerate recovery from inactivation, enhance the response to slow depolarisations, and enhance activation at the channel level, thereby producing hyperexcitability of small dorsal root ganglion (DRG) neurons, which include nociceptors, at the cellular level. Identification and functional profiling of additional NaV 1.8 variants are necessary to determine the spectrum of changes in channel properties that underlie DRG neuron hyperexcitability in these patients. Methods: Two patients with painful SFN were evaluated by skin biopsy, quantitative sensory testing, nerve conduction studies, screening of genomic DNA for mutations in SCN9A and SCN10A and electrophysiological functional analysis. Results: A novel sodium channel NaV 1.8 mutation G1662S was identified in both patients. Voltage-clamp analysis revealed that the NaV 1.8/G1662S substitution impairs fast-inactivation, depolarising the midpoint (V1/2 ) by approximately 7 mV. Expression of G1662S mutant channels within DRG neurons rendered these cells hyperexcitable. Conclusions: We report for the first time a mutation of NaV 1.8 which impairs inactivation, in patients with painful I-SFN. Together with our earlier results, our observations indicate that an array of NaV 1.8 mutations, which affect channel function in multiple ways, can contribute to the pathophysiology of painful peripheral neuropathy.